Method for preparing degradable mulching film from excess sludge extracellular polymeric substances
By combining the extracellular polymer in the remaining sludge with modified POSS materials, a degradable plastic film is prepared, which solves the environmental pollution problems caused by traditional plastic plastic films, and achieves low-cost and high-performance preparation of degradable plastic films, which has good biodegradability and economic benefits.
Patent Information
- Application Number
- CN202411917554.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-18
AI Technical Summary
It is difficult to develop a low-cost, degradable plastic film in the prior art, and the environmental pollution caused by traditional plastic plastic film has not been effectively solved.
By using the extracellular polymer in the remaining sludge as raw materials, the extracellular polymer-modified POSS material composite solution is prepared by adjusting the pH value of calcium oxide, heating extraction, purification, acidification and drying, combined with the modification and composite treatment of POSS materials, and finally, the degradable plastic film is prepared through the casting film formation process.
It has achieved the extraction of high-performance biological materials from the waste residual sludge at low cost, and prepared a degradable plastic film with good biodegradability, thermal insulation and moisturizing properties, reducing environmental pollution, reducing sludge disposal pressure, and having strong competitive economic advantages.
Smart Images

Figure CN119842083A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a degradable mulch film by utilizing extracellular polymers of excess sludge, and belongs to the technical field of sewage treatment resource utilization. Background Art
[0002] Sewage treatment plants produce a large amount of excess sludge while purifying sewage. If this excess sludge is not properly handled, it will cause serious ecological disasters. On the other hand, usable biological materials can be extracted from excess sludge and products with economic value can be produced. Therefore, the resource utilization of excess sludge can turn waste into treasure, which is the current policy orientation and development trend.
[0003] The residual sludge generated by sewage treatment plants is usually treated by incineration, landfill, etc. This treatment method is not only expensive, but also wastes land resources. If the sludge components can be treated as resources, the amount of sludge disposal can be reduced, and certain economic value can be generated, and better environmental benefits can be brought. Therefore, the resource recycling of residual sludge is a more promising route. Biomacromolecules such as proteins and polysaccharides secreted by bacteria in the process of purifying pollutants are the main components of the extracellular polymers of residual sludge. Due to different sewage quality and processes, the dry weight of extracellular polymers can account for 12% to 35% of the total dry weight of residual sludge. The extracted extracellular polymers are high-value biomacromolecules with great application potential in adhesives, building materials, papermaking and textiles, and soil improvement. However, extracellular polymers often exist only as auxiliary materials in these fields, and the amount of materials used is limited. Therefore, it is necessary to develop products with extracellular polymers as the main material.
[0004] Ground film can maintain soil moisture, increase soil temperature, and ensure stable agricultural production. However, the widely used plastic ground film has also generated a large amount of plastic pollution while increasing agricultural output. A large amount of non-degradable plastic pollution not only destroys soil structure and microbial activity, leading to crop yield reduction, but also decomposes into microplastics, enters the human body through water circulation, and endangers human health. Although degradable biomaterials have been used in the manufacture of ground films, their raw materials often come from biological fermentation, so the cost is much higher than plastic, which in turn limits the further promotion and application of degradable ground films. How to develop a low-cost degradable ground film is a technical problem that needs to be solved urgently. Summary of the invention
[0005] 1. Technical issues to be resolved
[0006] In order to solve the above problems in the prior art, the present invention provides a method for preparing a degradable mulch film by utilizing extracellular polymers of excess sludge.
[0007] (II) Technical solution
[0008] In order to achieve the above object, the main technical solutions adopted by the present invention include:
[0009] A method for preparing a degradable mulch film using extracellular polymers of excess sludge comprises the following steps:
[0010] S1, adjusting the pH value of the excess sludge to alkaline with calcium oxide powder, and extracting extracellular polymers under heating conditions;
[0011] S2, purifying, acidifying and drying the extracellular polymer extracted in step S1 to obtain extracellular polymer colloid;
[0012] S3, the POSS material and the sodium dodecyl sulfate solution are heated and stirred for the first time; then crotonic acid, acrylamine, allyl glycidyl ether, ammonium persulfate and sodium bisulfite are added, and heated and stirred for the second time to obtain modified POSS;
[0013] S4, adding purified extracellular polymer colloid, dimethyl carbonate, and dimethylacetamide to the modified POSS obtained above; adjusting the pH value of the solution and stirring and heating to obtain a composite solution of extracellular polymer-modified POSS material;
[0014] S5. Slowly cast the composite solution onto a polytetrafluoroethylene template and dry it in an oven to form a film.
[0015] In the method as described above, preferably, in step S1, the moisture content of the residual sludge is 91% to 95%; alkalinity refers to a pH value of 8 to 10; the heating conditions are a heating temperature of 70 to 85°C and stirring at a rate of 250 to 350 rpm, and a heating stirring time of 50 to 80 min.
[0016] In the method as described above, preferably, in step S1, the extraction of extracellular polymers is performed by taking the supernatant after centrifugation to obtain a solution containing extracellular polymers, wherein the centrifugation rate is 2500 rpm to 3500 rpm and the centrifugation time is 3 to 5 min.
[0017] As described above, preferably, in step S2, the purification conditions are: first adding palygorskite powder and stirring, then centrifuging, then adjusting the pH value of the extracellular polymer solution to 1.5-2 for acidification, centrifuging and drying the upper layer to obtain the extracellular polymer colloid; wherein the drying conditions are drying at 100-105°C for 1-2h.
[0018] Further, preferably, the dosage of palygorskite powder is 5 to 10 g / L, the particle size of the palygorskite powder is 20 to 400 μm, the stirring speed is 200 rpm to 300 rpm, and the stirring time is 15 to 30 min; hydrochloric acid is used to adjust the pH value of the extracellular polymer solution, the centrifugal speed is 8000 rpm to 8500 rpm, and the centrifugal time is 20 to 30 min.
[0019] As described above, preferably, in step S3, the POSS material is prepared by the following method: vinyltrimethoxysilane, acetone and hydrochloric acid are prepared by heating and refluxing in a water bath; vinyltrimethoxysilane, acetone and hydrochloric acid are added in a ratio of 20ml:1g:4ml, wherein the hydrochloric acid is a solution of concentrated hydrochloric acid and water in a volume ratio of 1:1, the temperature of the water bath is 40-50°C, the heating and refluxing time is 40-50h, and then the obtained POSS material is washed with anhydrous ethanol.
[0020] According to the method as described above, preferably, in step S3, the mass ratio of the POSS material to sodium dodecyl sulfate is 40-50:1, and the mass ratio of sodium dodecyl sulfate solution to water is 1:60-70; the temperature of the first heating and stirring is 70-80°C, the stirring rate is 150-250rpm, and the time is 30-50min.
[0021] According to the method as described above, preferably, in step S3, the amount of the butenoic acid, acrylamine and allyl glycidyl ether is carried out according to the mass ratio of POSS material to butenoic acid, acrylamine and allyl glycidyl ether of 1:0.23-0.35:0.3-0.45:0.4-0.45, and the mass ratio of POSS material to ammonium persulfate and sodium bisulfite is 1:0.175:0.044; the temperature of the second heating and stirring is 75-80°C, and the heating time is 3-6h.
[0022] According to the method described above, preferably, in step S4, the extracellular polymer colloid is added at a mass ratio of 5:1 to the POSS material, dimethyl carbonate and dimethylacetamide are added to the POSS material at a mass ratio of 1:1:20, the pH value of the solution is adjusted to 6, the heating temperature is 75-80°C, the stirring speed is 150-250rpm, and the stirring and heating time is 2-6h.
[0023] In the method as described above, preferably, in step S5, 0.15 g of the composite solution is poured per square centimeter onto the polytetrafluoroethylene film-forming plate; the drying temperature is 35-40° C., and the drying time is 15-48 hours.
[0024] (III) Beneficial effects
[0025] The beneficial effects of the present invention are:
[0026] The present invention provides a method for preparing a degradable mulch film using extracellular polymers of excess sludge, using extracellular polymers extracted from excess sludge as raw materials to prepare an economical biodegradable mulch film. The raw materials of the mulch film are extracted from waste excess sludge, which not only reduces the amount of excess sludge to be disposed of, but also obtains high-performance biological materials from it. The mulch film used to prepare the mulch has excellent biodegradability compared to traditional plastic mulch films, alleviating the environmental pollution caused by the use of traditional mulch films.
[0027] The present invention provides a method for preparing a degradable mulch film using extracellular polymers of excess sludge. The extracellular polymers extracted from the raw materials used contain a large number of cross-linkable functional groups such as amino groups and carboxyl groups, which increase the thermal insulation and moisture retention of the extracellular polymer mulch film and can meet the requirements of the national standard GB / T 35795-2017 fully biodegradable agricultural ground covering film. In addition, since the cost of the raw materials of the mulch film of the present invention is much lower than that of ordinary biodegradable mulch films, it has stronger competitiveness.
[0028] The present invention transforms the waste excess sludge into a biodegradable mulch film with excellent performance; while reducing the amount of excess sludge to be disposed of, it produces mulch film products with economic value, which is of great significance to the ecological environment and agricultural production. The extracellular polymers recovered from the excess sludge by the method provided by the present invention are used as products for sustainable agricultural development, which not only improves the social value of sewage treatment, but also further improves the efficiency of resource recovery, realizes carbon compensation and green sustainable agricultural development.
[0029] The mulch film obtained by the preparation method provided by the present invention has the advantages of low cost, natural degradation, no plastic pollution, etc., and also has excellent flexibility, biodegradability, and heat preservation and moisture retention properties. The present invention converts waste generated by sewage treatment into valuable products, while also avoiding environmental damage caused by plastic mulch films, and has important significance for environmental protection, economy and industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The process flow chart of preparing degradable mulch film by using extracellular polymers according to the present invention is as follows;
[0031] Figure 2 The schematic diagram of the modification of synthesized POSS particles;
[0032] Figure 3 is the infrared spectrum of the modified polyhedral oligomeric silsesquioxane;
[0033] Figure 4 Schematic diagram for the preparation of extracellular polymer-modified POSS particle composites;
[0034] Figure 5Schematic diagram of the mulch prepared for extracellular polymers.
[0035] [Description of Reference Numerals]
[0036] 1: The structural formula of vinyltrimethoxysilane;
[0037] 2: Structural formula of polyhedral oligomeric silsesquioxane;
[0038] 3: Structural formula of butenoic acid;
[0039] 4: Structural formula of allyl glycidyl ether;
[0040] 5: The structural formula of allylamine;
[0041] 6: Structural formula of modified polyhedral oligomeric silsesquioxane;
[0042] 7: Schematic diagram of modified polyhedral oligomeric silsesquioxane;
[0043] 8: Schematic diagram of extracellular polymers;
[0044] 9: Schematic diagram of the connection between extracellular polymers and modified POSS;
[0045] 10: Peptide bond binding group:
[0046] 11: Hydrogen bonding groups;
[0047] 12: Covalent bond linking group;
[0048] 13: Schematic diagram of extracellular polymer-modified POSS materials. DETAILED DESCRIPTION
[0049] The present invention relates to a process for large-scale extraction of extracellular polymers from excess sludge, and the preparation of degradable composite mulch films using the extracted extracellular polymers from excess sludge. The process includes the steps of extracting extracellular polymers from excess sludge, modifying extracellular polymers, preparing POSS materials, modifying POSS materials, preparing extracellular polymer-modified POSS material composites, and forming films of extracellular polymer-modified POSS material composites. Extracellular polymers are extracted from waste excess sludge, which contains abundant biomacromolecules including a large number of amino, carboxyl and hydroxyl groups. These groups are conducive to the cross-linking between molecules to form a network structure, thereby improving film-forming properties and tensile strength. In addition, the extracellular polymers are highly biodegradable, and the proteins and polysaccharides contained therein have a positive effect on the soil after the mulch films are decomposed. Therefore, the use of extracellular polymers to make mulch films is more environmentally friendly. The present invention transforms waste excess sludge into treasure, and extracts valuable biomaterials for sustainable agricultural production.
[0050] In summary, this process can partially extract and recycle extracellular polymers from sludge, reducing the pressure of sludge disposal. In addition, biodegradable mulch made of extracellular polymers is more environmentally friendly than traditional plastic mulch and has lower cost than existing biodegradable mulch.
[0051] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below through specific implementation modes in conjunction with the accompanying drawings.
[0052] Example 1
[0053] A process for preparing biodegradable mulch film using extracellular polymers extracted from excess sludge as raw materials, the process diagram of which is shown in FIG. Figure 1 As shown, the specific steps include:
[0054] S1. Transfer 20L of the residual sludge solution with a concentration of 9000mg / L to a centrifuge and centrifuge at 5500rpm for 5min; discard the supernatant after centrifugation, then add distilled water to prepare the substrate sludge into concentrated sludge with a moisture content of 91%; adjust the pH value of the concentrated sludge to 9.5 by adding calcium oxide powder to 2L of concentrated sludge; heat the solution temperature to 85℃ and stir at 350rpm; continue heating and stirring for 80min. After heating and stirring, transfer the solution to a centrifuge and centrifuge at 3500rpm for 5min. Transfer the upper layer of the solution containing extracellular polymers after centrifugation to a new clean container.
[0055] In this step, the sludge is first concentrated by centrifugation, and then the extracellular polymers are separated from the sludge phase under alkaline and heated conditions, dissolved in water, and separated from the sludge after another centrifugation. The added calcium oxide can not only adjust the pH of the solution, but the introduced calcium ions can also increase the dewatering performance of the sludge and reduce the speed and time required for centrifugation during separation.
[0056] S2. Add palygorskite powder with an average particle size of 300 μm to the solution containing extracellular polymers prepared above at a concentration of 6 g / L; stir continuously at a speed of 300 rpm for 20 min; then adjust the pH value of the extracellular polymer solution to 2 with 1 mol / L hydrochloric acid, and then transfer the solution to a centrifuge, centrifuge at a speed of 8000 rpm for 25 min, and dry the upper material at 105°C for 2 h to obtain an extracellular polymer colloid. The palygorskite powder used is used to adsorb impurities in the extracellular polymer. The palygorskite powder preferably has a particle size of 20 to 400 μm and has a higher specific surface area, which can improve the impurity adsorption efficiency. After the palygorskite powder purification treatment, the extracellular polymer is purified.
[0057] S3. Add 50g (51.6ml) of vinyltrimethoxysilane, 1000ml of acetone and 200ml of 6mol / L hydrochloric acid solution to the heating reflux device, and start the heating reflux equipment. The heating reflux device is a three-necked flask with a condenser. A glass condenser is inserted into the middle bottle mouth, and cooling circulating water is passed from bottom to top into the condenser to condense and reflux the solution vaporized by heating. One of the side bottle mouths of the three-necked flask is used to add raw materials, and is temporarily blocked with a rubber stopper after the raw materials are added. A thermometer is inserted into the other side bottle mouth to measure the solution temperature and is sealed with a rubber stopper. The capacity of the three-necked flask is 2L. Insert the condenser into the top of the three-necked flask, connect and open the condensation water circuit. Heat the solution in the three-necked flask to 45°C in a water bath, and continue heating and reflux for 48 hours to precipitate white particles.
[0058] After the reaction is finished, the white particles separated out in the solution are filtered out with 200 mesh stainless steel filter screens, i.e., POSS particles. The productive rate of the POSS raw material is 25.6% in this reaction. Afterwards, the POSS particles are put into 50 ml centrifuge tubes, and filled with anhydrous ethanol, and put into a rotary mixer and mix at a speed of 200 rpm for 10 min, for cleaning the POSS particles. Finally, the cleaned POSS particles are filtered out with 200 mesh stainless steel filter screens.
[0059] Vinyl trimethoxysilane is selected as the raw material in the present invention because its Si-O bond condensation reaction can form Si-O-Si as the core to form a POSS framework structure. Acetone and hydrochloric acid provide a reaction environment for the condensation reaction. Under the optimal conditions of vinyl trimethoxysilane, acetone and hydrochloric acid in a ratio of 20ml:1g:4ml, a heating temperature of 40-50°C and a heating reflux time of 40-50h, the yield is as high as 25.6%. Figure 2 As shown, in this reaction process, compound 1: vinyl trimethoxysilane is polymerized into compound 2: polyhedral oligomeric silsesquioxane (POSS). After the above-mentioned optimized optimal acidification and heating steps, vinyl trimethoxysilane forms a cage compound such as compound 2 with Si-O-Si bonds as the core. The peripheral side chains of the cage compound can be flexibly loaded with various groups to improve the mechanical properties, heat resistance and barrier properties of the material. Although POSS is commonly used in the modification of organic compounds, it is the first time to use it to modify extracellular polymers extracted from residual sludge.
[0060] The step of anhydrous ethanol cleaning in the present invention can effectively clean the residual vinyl trimethoxy silane, wherein the rotation speed of 200 rpm and the rotation time of 10 min are the minimum rotation speed and time that can clean the POSS particles. The present invention selects 200 mesh as the optimal aperture of the stainless steel screen, which can filter and retain more than 99% of the POSS particles and has the maximum filtration flow rate.
[0061] Add 10g of washed POSS particles into a new three-necked flask; then continue to add 0.25g of sodium dodecyl sulfate and 15g of distilled water to the three-necked flask; heat the solution to 70°C and stir at 200rpm for 40min. This process disperses the granular POSS material into the solution. Among them, sodium dodecyl sulfate acts as a co-solvent. Compared with other co-solvents such as isooctyl alcohol and ethanol, sodium dodecyl sulfate molecules have hydrophilic and hydrophobic groups of different properties. These two groups significantly promote the dissolution of POSS particles with multiple groups.
[0062] Then, 3g of acrylamine and 4.5g of allyl glycidyl ether were added to a three-necked flask; 2.3g of crotonic acid was weighed, diluted with 5g of distilled water, and the pH value was adjusted to 6 with 1mol / L hydrochloric acid and 1mol / L sodium hydroxide solution, and then added to the three-necked flask. Then, 1.75g of sodium persulfate and 0.44g of sodium bisulfite were added. Finally, the pH value of the solution was adjusted to 6, heated and stirred, and the solution temperature was maintained at 75°C for 4 hours to obtain modified POSS. In this process, under the action of heating and initiators such as ammonium persulfate and sodium bisulfite, Figure 2 In the figure, compound 2: the side chain of polyhedral oligomeric silsesquioxane is combined with compound 3: crotonic acid, compound 4: allyl glycidyl ether, and compound 5: acrylamine. Compound 2: polyhedral oligomeric silsesquioxane is modified and loaded with amino, carboxyl and epoxy groups for combining with various groups in extracellular polymers. The Si atoms on the vertices of the POSS cage structure can be embedded with various organic groups in the modifier through covalent bonds, and the connected active groups can be connected to polymers or polymer monomers through chemical reactions. In the present invention, acrylamine, allyl glycidyl ether and crotonic acid are modifiers, and these three modifiers all contain unsaturated carbon-carbon double bonds, which can be combined with the carbon-carbon double bonds in the POSS structure, and then loaded onto the POSS structure.
[0063] After the POSS material is modified through the above optimized optimal steps, compound 3: butenoic acid is loaded onto compound 2: polyhedral oligomeric silsesquioxane side chains to provide carboxyl groups, compound 4: allyl glycidyl ether is loaded onto compound 2: polyhedral oligomeric silsesquioxane side chains to provide epoxy groups, and compound 5: acrylamine is loaded onto compound 2: polyhedral oligomeric silsesquioxane side chains to provide amino groups. After the optimized modification steps, compound 6: modified polyhedral oligomeric silsesquioxane is generated. The infrared spectrum of compound 6: modified polyhedral oligomeric silsesquioxane is as follows: Figure 3As shown. The peaks from left to right are 3295: absorption peak caused by NH stretching in amino group; 1740: absorption peak caused by C=O stretching in carboxyl group; 1630: absorption peak caused by CN stretching in amino group; 1521: absorption peak caused by NH bending vibration in amino group; 1116: absorption peak caused by Si-O-Si stretching in POSS monomer; 1045: absorption peak caused by COC antisymmetric stretching vibration in alicyclic ether; 776 and 585 are C-Si stretching and Si-O-Si bending vibration in POSS, respectively. Among them, the optimized addition mass ratio of acrylamine, allyl glycidyl ether and butenoic acid is 3:4.5:2.3, which is the best ratio. Under the ratio of acrylamine, allyl glycidyl ether and butenoic acid of 3:4.5:2.3, the related groups in amino, carboxyl and alicyclic ether in the modified POSS material have the strongest absorption peaks in the infrared spectrum.
[0064] S4, add 50g of dry weight of the extracellular polymer colloid obtained in step S2 into the three-necked flask after the above reaction, then add 0.5g of dimethyl carbonate and 0.5g of dimethylacetamide as peptide bond activators, and then adjust the pH value of the solution to 6 with 1mol of hydrochloric acid and 1mol of sodium hydroxide. Finally, heat and maintain the temperature at 75°C at a stirring speed of 200rpm for 3 hours. In this reaction, compound-7: modified polyhedral oligomeric silsesquioxane and compound-8: extracellular polymer are connected to each other, as shown in the schematic diagram Figure 4 Figure 9 is a schematic diagram of the connection between extracellular polymer and modified POSS. The chemical groups that play a role in connection include: 10: peptide bond binding group, 11: hydrogen bond connecting group and 12: covalent bond linking group. The final compound 13: extracellular polymer-modified POSS material is formed, such as Figure 5 As shown. Among them, the pH, temperature, reaction time and activator addition amount in this step are optimized optimal parameters. Under this parameter, the ground film formed by the modified POSS material and extracellular polymers has the best breaking elongation of 287.1%.
[0065] S5, pour the mixed solution obtained in S4 onto a 40 square centimeter polytetrafluoroethylene film-forming plate. The pouring speed is 10 grams of extracellular polymer dry weight / min. Then transfer the film-forming plate to an oven and dry it at a drying temperature of 35°C for 48 hours. Finally, the extracellular polymer is dried to form a ground film.
[0066] According to the method of GB / T 35795-2017 Fully biodegradable agricultural ground covering film, the mechanical properties, biodegradability, moisture retention and thermal insulation properties of the prepared ground film were tested. The breaking elongation of the ground film was measured to be 287.1%, and the water vapor permeability was 612g / (m 2·24h). Its performance meets the GB / T 35795-2017 standard for fully biodegradable agricultural ground covering films.
[0067] The biodegradability rate was determined according to the method described in (Li Jinhai, Xu Yuanwei, Zhao Jun, et al. Preparation and performance study of potato starch-based degradable mulch film [J]. Journal of Guizhou University: Natural Science Edition, 2020, 37(4):5.), and the 60-day degradability rate of the mulch film prepared above was 91.2%.
[0068] Thermal insulation performance test: The same amount of soil was placed in beakers of the same size, and the beakers were left uncovered or covered with the mulch prepared by the above method, and placed outdoors. The temperature of the soil in the middle was measured using a thermometer at 12 noon. The soil temperature of the mulch prepared by the above method was found to be 2.3°C higher than that of the soil not covered with the mulch.
[0069] Moisture retention performance test: Put the same amount of soil in beakers of the same size, and place them outdoors without any covering or with the mulch prepared by the above method. After 7 days, weigh the same amount of soil in the middle and place it in an oven to dry to constant weight. According to the formula: moisture content = (soil mass before drying - soil mass after drying) / soil mass after drying. It was measured that the soil moisture content of the mulch prepared by the above method was 4.26% higher than that of the soil not covered with the mulch.
[0070] It can be seen that the mulch film prepared by the present invention has a higher degradation rate and heat preservation and moisture retention properties.
[0071] Comparative Example 1
[0072] The following steps can be used to directly synthesize mulch films from extracellular polymers: (1) Take the residual sludge with a sludge concentration of 20g / L, centrifuge and discard the supernatant, and then dilute the sludge at the bottom with the same volume of distilled water; (2) Use 1mol / L sodium hydroxide to adjust the pH value of the diluted sludge to 9, then heat the solution to 80°C and stir at 200rpm for 30 minutes; (3) Centrifuge the stirred and heated solution at 6000rpm for 10 minutes, take out the supernatant and put it in a new beaker, and adjust the pH of the solution to 2.5 with 1mol hydrochloric acid. (4) Centrifuge the acidified solution at 6000rpm. Take the supernatant containing extracellular polymers after centrifugation and evaporate it into extracellular polymer colloid; (5) Spread the extracellular polymers onto a polytetrafluoroethylene film-forming plate and dry it to form a film.
[0073] Because extracellular polymers are extracted from waste sludge, they contain impurities and lack effective connections between macromolecules. Therefore, if extracellular polymers are directly used to prepare biodegradable ground films, they have disadvantages such as poor service life and low ductility, which is far from meeting the national standard GB / T 35795-2017 fully biodegradable agricultural ground covering film.
[0074] The embodiment of the present invention first uses palygorskite powder for the purification of extracellular polymers of excess sludge, and effectively removes impurities in extracellular polymers by optimizing parameters such as the amount of palygorskite powder and particle size. By this means, the light transmittance and other parameters of the biodegradable mulch prepared from the extracellular polymers of excess sludge meet the requirements of the national standard. In addition, according to the molecular characteristics and functional group types of the extracellular polymers of excess sludge, acrylamide, allyl glycidyl ether and crotonic acid are used for the first time to modify the POSS raw material; then specific functional groups are loaded on the POSS molecules, and then the POSS molecules loaded with specific functional groups are combined with the relevant groups in the extracellular polymers, and the macromolecules in the extracellular polymers are connected to each other to prepare the mulch. The effective life, appearance defects, and elongation at break methods in GB / T 35795-2017 are used for determination. The effective lifespan is 43 days for the direct film formation of the extracellular polymer in comparative example 1, while 82 days for the modified film formation of the extracellular polymer in Example 1 of the present application; the appearance defects are 23 / 100cm for the direct film formation of the extracellular polymer in comparative example 1. 2 The extracellular polymer modified film in Example 1 is 3 / 100cm 2 ; Breaking elongation: the direct film-forming exopolymer of comparative example 1 is 162%, and the modified film-forming exopolymer of example 1 is 287.1%. It can be seen that compared with the mulch film directly prepared by exopolymer, the mulch film prepared by the method of the present invention has better performance.
[0075] In addition, the biodegradable mulch prepared by using the extracellular polymers of excess sludge provided by the present invention has a lower preparation cost than the existing biodegradable mulch. The main raw materials of conventional biodegradable mulch include: polylactic acid (PLA), polyhydroxyalkanoate polymers (PHA) and other biomacromolecules. These materials are usually synthesized by characteristic microorganisms. Under a specific artificial environment, the relevant microorganisms use carbon sources such as starch and glucose as substrates to convert them into polymer biomaterials. In this process, the substrate consumption, cultivation and extraction of microorganisms require a lot of costs, resulting in a high price of the produced biopolymer materials (see Zhu Wenwen. Research Progress of Biodegradable Plastics [J]. Rural Science Experiment, 2017 (4): 2. DOI: CNKI: SUN: NCKX.0.2017-04-102.). For example, the industrial production of PLA requires the production of lactic acid using raw materials such as corn through a biofermentation method, followed by filtration and purification to obtain lactic acid monomers, and finally obtaining polylactic acid through harsh reaction conditions such as high temperature, pressure change and catalysts (see Yan Dongyu. Technical Analysis of Polylactic Acid Market [J]. Information Recording Materials, 2023, 24(9):8-11). Therefore, the price of conventional biodegradable mulch is often high due to the high cost of raw materials. In contrast, residual sludge is a waste product in the biological treatment of sewage. The production of extracellular polymers using residual sludge as raw material is a process of turning waste into treasure, and the raw material cost of residual sludge does not need to be paid. Compared with materials such as PLA and PHA, the production of extracellular polymers saves a lot of raw material preparation costs. Raw material costs account for a large part of the manufacturing cost of biodegradable mulch, so the preparation of degradable mulch using residual sludge extracellular polymers as raw materials can effectively reduce the preparation cost.
[0076] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any person skilled in the art can use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a degradable mulch film using extracellular polymers of excess sludge, characterized in that: It includes the following steps: S1, adjusting the pH value of the excess sludge to alkaline with calcium oxide powder, and extracting extracellular polymers under heating conditions; S2, purifying, acidifying and drying the extracellular polymer extracted in step S1 to obtain extracellular polymer colloid; S3, the POSS material and sodium dodecyl sulfate solution are heated and stirred for the first time; then crotonic acid, acrylamine and allyl glycidyl ether, ammonium persulfate and sodium bisulfite are added, and heated and stirred for the second time to obtain modified POSS; S4, adding purified extracellular polymer colloid, dimethyl carbonate, and dimethylacetamide to the modified POSS obtained above; adjusting the pH value of the solution and stirring and heating to obtain a composite solution of extracellular polymer-modified POSS material; S5. Slowly cast the composite solution onto a polytetrafluoroethylene template and dry it in an oven to form a film.
2. The method according to claim 1, characterized in that In step S1, the water content of the excess sludge is 91% to 95%; alkalinity refers to a pH value of 8 to 10; the heating conditions are a heating temperature of 70 to 85°C, stirring at a speed of 250 to 350 rpm, and a heating stirring time of 50 to 80 minutes.
3. The method according to claim 1, characterized in that In step S1, the extracellular polymer is extracted by taking the supernatant after centrifugation to obtain a solution containing the extracellular polymer, wherein the centrifugation rate is 2500 rpm to 3500 rpm and the centrifugation time is 3 to 5 min.
4. The method according to claim 3, characterized in that In step S2, the purification conditions are as follows: first, palygorskite powder is added and stirred, then the pH value of the extracellular polymer solution is adjusted to 1.5-2 for acidification, and the upper layer is centrifuged and dried to obtain the extracellular polymer colloid; wherein, the drying conditions are drying at 100-105°C for 1-2 hours.
5. The method according to claim 4, characterized in that The dosage of palygorskite powder is 5-10 g / L, the particle size of the palygorskite powder is 20-400 μm, the stirring speed is 200 rpm-300 rpm, and the stirring time is 15-30 min; hydrochloric acid is used to adjust the pH value of the extracellular polymer solution; the centrifugal speed is 8000 rpm-8500 rpm, and the centrifugal time is 20-30 min.
6. The method according to claim 1, characterized in that In step S3, the POSS material is prepared by the following method: vinyltrimethoxysilane, acetone and hydrochloric acid are prepared by heating and refluxing in a water bath; vinyltrimethoxysilane, acetone and hydrochloric acid are added in a ratio of 20ml:1g:4ml, the hydrochloric acid is a solution of concentrated hydrochloric acid and water in a volume ratio of 1:1, the temperature of the water bath is 40-50°C, the heating and refluxing time is 40-50h, and then the obtained POSS material is washed with anhydrous ethanol.
7. The method according to claim 1, characterized in that In step S3, the mass ratio of the POSS material to sodium dodecyl sulfate is 40-50:1, and the mass ratio of sodium dodecyl sulfate solution to water is 1:60-70; the temperature of the first heating and stirring is 70-80°C, the stirring rate is 150-250rpm, and the time is 30-50min.
8. The method according to claim 1, characterized in that In step S3, the amount of crotonic acid, acrylamine and allyl glycidyl ether is added according to the mass ratio of POSS material to crotonic acid, acrylamine and allyl glycidyl ether of 1:0.23-0.35:0.3-0.45:0.4-0.45, and the mass ratio of POSS material to ammonium persulfate and sodium bisulfite is 1:0.175:0.044; the temperature of the second heating and stirring is 75-80°C, and the heating time is 3-6h.
9. The method according to claim 1, characterized in that In step S4, the extracellular polymer colloid is added at a mass ratio of 5:1 between the extracellular polymer colloid and the POSS material, dimethyl carbonate and dimethylacetamide are added at a mass ratio of 1:1:20 to the POSS material, the pH value of the solution is adjusted to 6, the heating temperature is 75-80°C, the stirring speed is 150-250rpm, and the stirring and heating time is 2-6h.
10. The method according to claim 1, characterized in that In step S5, 0.15 g of the composite solution is poured per square centimeter onto the polytetrafluoroethylene film-forming plate; the drying temperature is 35-40° C. and the drying time is 15-48 hours.